NEOLIBERALISMO Y PRECARIEDAD LABORAL EN EL ESTADO ARGENTINO (1990-2007) - Guimenez, Sandra (Universidad de Costa Rica, 2013)
This article describes the emergence and institutionalization of precarious labor relations in the Argentine administration throughout the nineties. In this regard, it provides information about how job insecurity settled within this institutional space, taking special interest on how the workers themselves experiencing new wor-king conditions.